A new discontinuous impact model with finite collision duration. (1st March 2022) - Witkowski, Krzysztof; Kudra, Grzegorz; Awrejcewicz, Jan
Highlights: Experimental and mathematical models of a one-degree-of-freedom impact oscillator are presented. A new discontinuous impact model with finite collision duration is developed. The impact model is validated during numerical and experimental bifurcation analysis of the investigated system. Abstract: In the work it is proposed a new discontinuous impact model based on the restitution coefficient and the finite duration of the collision, which are functions of the velocity before the collision. The model was validated during modelling, experimental and simulation studies of the bifurcation dynamics of an oscillator of one-degree-of-freedom with a one-sided limiter. The simulation results using the new discontinuous impact model were compared with numerical solutions obtained with the use of the continuous five-parameter Hunt-Crossley model assuming the obstacle compliance. It was shown that the new discontinuous model produces results that are as realistic and consistent with the experimental data as the compliant impact model. Moreover, the significance of the dependence of the restitution coefficient on the speed before the collision and the contact time during the collision in obtaining a good agreement of the simulation results with the experimental data were shown.